Pengembangan Soft Skills Siswa Melalui Pendekatan Social-Emotional Learning (Sel) Pada Materi Senyawa Hidrokarbon Dan Turunannya - Utami, Wilujeng Wachyu; Erdawati; Rahmawati, Yuli (LPPM Universitas Negeri Jakarta, 2024)
his research is a classroom action research conducted in class XI of 2nd Electrical Engineering Program at SMK Kemala Bhayangkari 1 Jakarta in the second semester of the academic year 2015 / 2016. The research focuses on developing soft skills with social-emotional learning approaches on the material hydrocarbon compounds and their derivatives. Soft skills development through its core competencies SEL includes Self Awareness, Self Management, Social Awareness, Relationship Management, Responsible Decision Making. Think Write Pair Share Method (TWPS) is used to integrate SEL on chemistry learning. The techniques of data collection for soft skills development conducted through Social-Emotional Learning Survey (SELS) questionnaires, which has been developed under the SEL rubric that has been validated, reflective journals, observation and interviews. Internal validation (credibility) was conducted to test the accuracy of the research data, including prolonged engagement, persistent observation, progressive subjectivity and member checking. The data analysis concluded that there was development soft skills of students who can be seen from the indicator (1) Work Confidence; (2) Persistence; (3) Organisation; (4) Resilence; (5) Relationship Management; (6) Social Awareness; (7) Responsible Decision Making; (8) Concept Training Students; (9) The task of the Project. The results of this study have provided learning experiences and new perceptions towards learning chemistry. But the application of Social-Emotional Learning approach will be more quality if it received support from several parties, such as policy makers, schools and parents.